Proposed low-energy absolute calibration of nuclear recoils in a dual-phase noble element TPC using D-D neutron scattering kinematics - Verbus, J.R.; Rhyne, C.A.; Malling, D.C.; Genecov, M.; Ghosh, S.; Moskowitz, A.G.; Chan, S.; Chapman, J.J.; de Viveiros, L.; Faham, C.H.; Fiorucci, S.; Huang, D.Q.; et al. (My University, 2017)
We propose a new technique for the calibration of nuclear recoils in large noble element dual-phase time projection chambers used to search for WIMP dark matter in the local galactic halo. This technique provides an $\textit{in situ}$ measurement of the low-energy nuclear recoil response of the target media using the measured scattering angle between multiple neutron interactions within the detector volume. The low-energy reach and reduced systematics of this calibration have particular significance for the low-mass WIMP sensitivity of several leading dark matter experiments. Multiple strategies for improving this calibration technique are discussed, including the creation of a new type of quasi-monoenergetic 272 keV neutron source. We report results from a time-of-flight based measurement of the neutron energy spectrum produced by an Adelphi Technology, Inc. DD108 neutron generator, confirming its suitability for the proposed nuclear recoil calibration.